Can a Female Donor for a Male Recipient Decrease Relapse Rate for Patients with AML Treated with Allogeneic Hematopoietic Stem Cell Transplantation? - Kongtim, Piyanuch (Biol Blood Marrow Transplant, 2014)
The mismatched minor histocompatibility antigens present on Y chromosome (H-Y) in male recipients receiving stem cells from female donors may contribute to graft-versus-leukemia effect (GVL) and results in reduce relapse rate especially in patients with high-risk disease. We retrospectively compared the outcomes of male AML patients who received an allogeneic hematopoietic stem cell transplant (HSCT) from female donors (F-M) (174 patients) versus other gender combinations (667 patients). Median age was 50 years (range 18–74 years). For the whole group, the one-year cumulative incidence of relapse was significantly lower in F-M group (34.1% versus 41.3%, p=0.044) while non-relapse mortality (NRM) was higher (23.2% versus 15.7%, p=0.004). For patients younger than 50 years beyond first complete remission, the F-M group was associated with lower relapse rate (42.5% versus 55.2%, p=0.045) whereas NRM was not significantly different (35.8% versus 25.5%, p=0.141). Although survival was not significantly improved, transplantation from a female donor for male recipient was associated with a lower relapse rate. When relapse is most common concern for treatment failure, especially for younger patients, a female donor for a male recipient might be beneficial to decrease relapse rate post-transplant. Future studies are needed to explore how H-Y mismatch may improve survival post-transplant.